A Comparison of Divergent Thinking Abilities Between Healthy Elderly Subjects and MCI Patients: Preliminary Findings and Implications - Fusi, Giulia; Ferrari, Elena; Zanetti, Marina; Crepaldi, Maura; Bersanini, Carol; Paladino, Anna; Colautti, Laura; Rozzini, Luca; Antonietti, Alessandro; Rusconi, Maria Luisa (Frontiers in Psychology, 2020)
Objective Divergent thinking (DT) has attracted research interest because of its potential role in early diagnosis and rehabilitation programs for patients affected by neurodegenerative diseases. Recently, DT has received even more attention because of its proven relationship with cognitive reserve (CR) and the possibility of a standardized assessment. However, few studies have investigated this ability in dementia patients, and even less is known about patients affected by Mild Cognitive Impairment (MCI). Thus, this study aims to investigate DT abilities in MCI patients. Methods A total of 25 MCI patients and 25 healthy controls subjects (HC; from a random selection of 50) matched for age, gender, and educational level were enrolled. General cognitive functioning was measured by the Montreal Cognitive Assessment (MoCA), while the Abbreviated Torrance Test for Adults (ATTA) was selected to measure DT. Results MANOVA analysis did not reveal any significant differences in DT abilities between MCI patients and HC except for the figural indicator score. A logistic hierarchical regression analysis revealed that the figural indicator score added an 8% of accuracy in the prediction of the group variable over the general cognition measure (MoCA). Conclusion MCI patients seem to perform significantly worse than HC only in the figural DT score and this evidence has significant practical implications. First, that figural DT seemed to decrease even earlier than verbal DT and could therefore be taken into account for early diagnosis of MCI patients. On the contrary, the sparing of all the other DT skills (such as verbal DT skills, fluency, flexibility, originality, and elaboration) may suggest that, given its relationship with CR, verbal DT could instead be considered a possible target for prevention or early cognitive stimulation interventions.